Communicative competence of a child with cerebral palsy and mild intellectual disability - Wiecha, Dominika; Zając, Ewelina (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
In the article, the communicative competence of a 12 year old girl with cerebral palsy and mild intellectual disability was characterised. These developmental disorders exert a significant impact on child’s skills in the field of speech expression and perception. Moreover, they lead to speech disorders: oligophasia and dysarthria. The case study method was used to conduct the research. In the first part of this article the authors described two issues: cerebral palsy and intellectual disability. They indicated the causes, as well as the most common symptoms of these developmental disorders. In the next part the authors provided an extensive description of various diagnostic tests. They enabled the researchers to explore, among others, speech expression and perception, as well as phonematic hearing. The results of these different tests were thoroughly analysed. Consequently, it has been proved that the level of child’s linguistic and communication skills corresponds to the results achieved by children with similar deficits and disorders.